2022
DOI: 10.1111/ajt.16709
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses following tocilizumab therapy to desensitize HLA-sensitized kidney transplant candidates

Abstract: Kidney transplant candidates (KTCs) who are HLA highly sensitized (calculated panel‐reactive alloantibodies >95%) have poor access to deceased kidney transplantation. In this single‐center prospective study, 13 highly sensitized desensitization‐naïve KTCs received IV tocilizumab (8 mg/kg) every 4 weeks. We evaluated tolerability as well as immune responses, that is, T cell, B cell, T follicular helper (Tfh) subsets, blood cytokines (IL‐6, soluble IL‐6 receptor‐sIL‐6R‐, IL‐21), blood chemokines (CXCL10, CXCL13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(82 reference statements)
1
19
0
Order By: Relevance
“…It is widely known that immune response is a leading factor affecting the function of allograft after kidney transplantation [ 29 , 30 ]. In this study immune-related BP terms, e.g., interferon-gamma-mediated signaling pathway, type I interferon signaling pathway, immune response, antigen processing and presentation, etc.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely known that immune response is a leading factor affecting the function of allograft after kidney transplantation [ 29 , 30 ]. In this study immune-related BP terms, e.g., interferon-gamma-mediated signaling pathway, type I interferon signaling pathway, immune response, antigen processing and presentation, etc.…”
Section: Resultsmentioning
confidence: 99%
“…It has been showed that TCZ significantly and nonspecifically reduce the IgG synthesis in highly sensitized kidney transplant recipients treated for cABMR (23). However, in highly sensitized kidney transplant candidates, tocilizumab as a monotherapy limited B cell maturation but however, it had almost no effect on anti-HLA alloantibodies (24). Chandran et al conducted a randomized controlled clinical trial of clinically stable kidney transplant recipients on calcineurin inhibitor, mycophenolate mofetil, and prednisone, with subclinical graft inflammation noted on surveillance biopsies during the first-year post-transplant: they were randomized to receive either TCZ (8 mg/kg every 4 weeks, six infusions) or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results must be weighed up against the modest overall effect of TCZ as the single desensitization strategy [ 9 , 10 ]. Previous studies have suggested that the response to TCZ in rheumatoid arthritis is greater when sIL-6R levels are low [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only half of these patients were able to receive a transplant (5/10 patients) and one patient developed antibody-mediated rejection after transplantation [ 5 ]. In our recently published experience, TCZ as a desensitization therapy failed to induce a clinically significant reduction in anti-HLA antibody mean fluorescent intensity (MFI) [ 9 ], but limited B-cell maturation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%